QUANTITATIVE ESTIMATION OF DIACETYLMORPHINE BY PREPARATIVE TLC AND UV SPECTROSCOPY - Khan, L; Siddiqui, M T; Ahmad, N; Shafi, N (Biological Sciences - PJSIR, 2001)
A simple and efficient method for the quantitative estimation of diacetylmorphine in narcotic products has been described. Comparative TLC of narcotic specimens with standards showed presence of morphine, monoacetylmorphine, diacetyl- morphine papaverine and noscapine, Resolution of the mixtures was achieved by preparative TLC. Bands corresponding to diacetylmorphine scraped, eluted UV absorbtion of extracts measured and contents quantified.